Analisis Kinerja Instalasi Pengolahan Air Limbah Pada Pusat Perbelanjaan di Kota Surabaya (Studi Kasus: Mal X dan Y) - Mochamad Rifki Fiakhsani Taqwim; Muhammad Faisal Fadhil (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Increased activity in shopping centres generates liquid waste that has the potential to pollute the environment if not properly managed. The assessment was carried out by measuring the efficiency of the wastewater treatment plant in treating wastewater quality parameters such as Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Total Suspended Solids (TSS) and pH in accordance with the quality standards set by the government. The research methodology included field observations, laboratory analyses and interviews with STP managers. The results showed that the results of the wastewater quality standard test at the wastewater treatment plant of Mall Y had met the domestic wastewater quality standard, but Mall X had parameters that did not meet the quality standard. Factors such as the level of efficiency and treatment capacity of the STP and the level of maintenance of the equipment can significantly affect performance. These findings are expected to provide a reference for shopping centre managers to improve wastewater management and comply with applicable environmental regulations, as well as contribute to sustainable environmental management.